M – cognocracy : building participatory democracy through the electronic voting and mobile ICT - Brys, Carlos Roberto (2021)
Fil: Brys, Carlos Roberto. Universidad Nacional de Misiones. Facultad de Ciencias Económicas. Departamento de Informática; Argentina.